Quantitative Study of Unemployment Rates in Java Provinces: VECM Panel Data Analysis - Rizal Mustofa; Wahyu Hidayat Riyanto (Jurnal Ekonomi Pembangunan, 2026)
This study was conducted to analyze the impact of GRDP and RLS on unemployment rates in several provinces on the island in the short and long term. This is quantitative research. This study uses the PVECM analysis method using panel data from 6 provinces on the island of Java from 2003 to 2024. The results of the PVECM analysis of GRDP in the short term have a significant effect on the unemployment rate, and in the long-term PVECM RLS analysis, it has a significant negative effect on the unemployment rate. Then, in the long term, GRDP and RLS have a significant effect on the unemployment rate.